Signifikansi memahami Logika Dasar - M. idrus H. Ahmad (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2012)
asically human being poses intelligence as a device to think in order to achieve their purposes in life whether personal, group, or communal purposes. To think without a depth and serious process is known as “ logical naturalist”. It means that one thinks in a very simple and natural ways. When intelligence contemplates a complex problem, it is called “logical artificial” that uses tight logical procedure and logical science or is known in Islam as “Mantiq”. One of fundamental differentiation between human being from animal is that the ratio potential (natiq). The ratio activities on the subject, understanding written or spoken word (lafaz), defining, proposing, opposing, sampling or analogy, forming and syllogism result to a true and precise conclusion.